The Westerners in contact with the Indian Ocean peoples : a contribution to the history of cultural connections in the Hellenistic period (4th century B.C.-1st century B.C.) - (:unkn) unknown (My University, 2019)
A connected history of the ancient Indian Ocean may appear out of the reach of historians: the traces of contacts between Asia, East Africa and the Mediterranean seem to have vanished with documents. This paper is an attempt to show that the dramatic lack of evidence does not lead to a desperate situation. Five stories reporting cultural encounters – ranging from cordial meetings to true confrontations – have been selected. It emerges that classical documents, although flawed and biased, depict a variety of cultural connections between Greeks and eastern peoples, and a vibrant period of Indian Ocean history.
Keywords: African Research